2010
DOI: 10.1038/modpathol.2009.186
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A and MTAP deletions in peritoneal mesotheliomas are correlated with loss of p16 protein expression and poor survival

Abstract: Homozygous deletion of CDKN2A (p16) is one of the most common genetic alterations in pleural mesotheliomas, occurring in up to 74% of cases. MTAP resides in the same gene cluster of the 9p21 region and is co-deleted in the majority of CDKN2A deleted cases. This study examines the genetic alterations in peritoneal mesotheliomas, which may have a different pathogenesis than their pleural counterparts. Twenty-six cases of peritoneal mesotheliomas in a triplicate tissue microarray were studied. Dual-color fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 32 publications
8
84
1
2
Order By: Relevance
“…40,41 Despite the differences between peritoneal and pleural mesotheliomas, previous studies have demonstrated homozygous CDKN2A deletions in malignant mesothelioma are a poor prognostic indicator regardless of site. 22,25,32 Consistent with these reports, we found that patients with peritoneal mesothelioma harboring a homozygous CDKN2A deletion had decreased PFS and OS. In addition, patients with a hemizygous NF2 loss also exhibited poor PFS and OS.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…40,41 Despite the differences between peritoneal and pleural mesotheliomas, previous studies have demonstrated homozygous CDKN2A deletions in malignant mesothelioma are a poor prognostic indicator regardless of site. 22,25,32 Consistent with these reports, we found that patients with peritoneal mesothelioma harboring a homozygous CDKN2A deletion had decreased PFS and OS. In addition, patients with a hemizygous NF2 loss also exhibited poor PFS and OS.…”
Section: Discussionsupporting
confidence: 90%
“…However, the prevalence of homozygous CDKN2A deletions and hemizygous NF2 loss in peritoneal mesotheliomas is less than those reported for pleural mesotheliomas. 16,[21][22][23]26,32 In addition, the most frequent abnormality in peritoneal mesotheliomas was the loss of BAP1 protein expression rather than homozygous CDKN2A deletions. An explanation for the disparities between peritoneal and pleural mesotheliomas remains elusive, but not surprising as both entities are clinically and pathologically distinct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the presence of p16 homozygous deletion correlates with a shorter survival in patients with malignant mesotheliomas. 85,90,91 There is also a correlation between p16 protein loss, as demonstrated by immunohistochemistry, and a poor prognosis with increased risk of death in peritoneal mesothelioma, but the association is not as strong. 55,90 There are no molecular markers to help distinguish malignant mesotheliomas from carcinomas or sarcomas on formalin-fixed, paraffin embedded tissue.…”
Section: Bg8mentioning
confidence: 99%